Motivación y su incidencia en el aprendizaje del área de lengua y literatura de los estudiantes de cuarto y quinto año de educación básica de la Escuela John. F. Kennedy del cantón Mocache - Ube Pinto, Martha Eveliza (2018)
This project was carried out to learn how motivation influences the teaching and learning process in students in the area of language literature. The research carried out determined that the project has the scope necessary for its execution the series of questions asked in the survey and the Interviews with teachers and students show that there is no motivation to learn language and most students believe that techniques should be applied to motivate them to learn more about this subject because during the development of classes in this area the teaching is monotonous and in certain cases it becomes boring and we call attention to learn more but know the importance that it has. For the elaboration of the guide, each technique was taken into account with a specific objective that is expected to be achieved with a proposal that contains various tools that promote mental agility, verbal, creativity, word play motivating learning in a fun way so that the student knows the importance of the subject and that it is not difficult at all and that he can develop efficiently with excellent results.